Ingestión y digestión de siete especies de microalgas por larvas de Strombus gigas (Mesogastropoda: Strombidae) - Patiño Súarez, Victoria; Aldana Aranda, Dalila (Revista de Biología Tropical, 2000)
The potential nutritional value of seven microalgal diets as measured by their ingestibility and digestibility to queen conch Strombus gigas larvae was tested with 30 day old larvae reared at 28°C and fed at 1000 cells ml-1. The algae were Tetraselmis suecica, Tetraselmis chuii, Isochrysis aff. galbana, Dunaliella tertiolecta, Chlamydomonas coccoides, Chaetoceros sp. and Thalassiosira fluviatilis. Ingestion and digestion were measured by the four nutritional stages studied with epifluorescence microscopy with live larvae. Temporal and absolute indices showed that arvae fed Chaetoceros sp. and T. fluviatilis had lower ingestion and digestion levels. The other algae are recommend to feed S. gigas larvae.